A novel profibrotic mechanism mediated by TGFβ‐stimulated collagen prolyl hydroxylase expression in fibrotic lung mesenchymal cells. Issue 3 (8th April 2015) - Luo, Yongfeng; Xu, Wei; Chen, Hui; Warburton, David; Dong, Rachel; Qian, Bangping; Selman, Moisés; Gauldie, Jack; Kolb, Martin; Shi, Wei
Abstract Idiopathic pulmonary fibrosis is a severe chronic lung disease with a high mortality rate. Excessive TGFβ signalling is recognized as a central player in lung fibrosis. However, the related mechanisms remain unclear. Herein we used a novel Tbx4 lung enhancer‐driven Tet‐On transgenic system to inhibit TGFβ signalling in mouse lung‐resident mesenchymal cells at different stages of bleomycin‐induced fibrosis, by conditionally knocking out TGFβ receptor II or expressing a dominant‐negative TGFβ receptor II. Abrogation of mesenchymal TGFβ signalling markedly attenuated bleomycin‐induced fibrotic pathology, which was independent of altered early inflammation. Furthermore, a novel TGFβ downstream target gene P4HA3 (an α‐subunit of collagen prolyl hydroxylase) was identified, and its expression was significantly increased in fibroblastic foci of both bleomycin‐induced fibrotic mouse lungs and idiopathic pulmonary fibrosis patients' lungs. The relationship between activated TGFβ signalling, up‐regulation of P4HA3 and increased hydroxyproline/collagen production was further verified in cultured lung fibroblasts. Moreover, inhibition of collagen prolyl hydroxylase by pyridine‐2, 5‐dicarboxylate attenuated TGFβ‐stimulated collagen production in both cultured fibroblasts and bleomycin‐induced mouse lung fibrosis. These data indicate that increased expression and activity of collagen prolyl hydroxylase is one of the important mechanisms underlying TGFβ‐mediated profibrotic effects. Inhibition of collagen prolyl hydroxylase may be a new, promising approach for preventing and treating pulmonary fibrosis. Copyright © 2015 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.